Faktor Risiko Potensial Mencegah Meningkatnya Konsumsi Rokok Elektrik di Kalangan Remaja Indonesia Usia 13 Hingga 15 Tahun - Kusnali, Asep; Vebby Amelia Edwin; Endang Indriasih; Suryati, Tati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Data showing a significant increase trend in sales of electronic cigarettes in Indonesia and users aged ≥ 15 years have increased tenfold to 6.6 million in 2021, and there has been no e-cigarette regulation. The purpose of the study is to provide evidence to support policies intended for increasing the number of electric smokers. Using data from the 2019 Global Youth Tobacco Survey with national representation. Simple and multiple logistic regression analyses (p < 0.05) were performed. The analysis states: 15% of youth 13-15 years old use e-cigarettes and most users are boys 13 years old, with a weekly disposable income below IDR 50,000. Multivariate analysis shows; friends or shop workers who provide e-cigarettes or attend events promoting tobacco products have a 15-fold greater influence on adolescents than the reference group. When compared to not seeing the advertisements, e-cigarette advertisements on the streets/stores/TV/ internet have the potential to increase adolescent motivation by 8 times. Nonsmokers who have tried tobacco products are potentially three times more likely to be interested in e-cigarettes than those who have never tried them. Adolescent smokers are twice as likely as nonsmokers to use e-cigarettes, and close friends who smoke are twice as likely as nonsmokers to influence e-cigarette use. Information shows that the previous Tobacco Advertising Promotion and Sponsorship Policy was ineffective, it needed to be strengthened with a total ban. It is critical to strengthen smoking cessation efforts, as well as raise parental and community awareness of the dangers of consuming tobacco products.